MODIFIKASI LIMBAH PASIR SILIKA PT. DPL DENGAN GUGUS AMINE MENGGUNAKAN METODE IN SITU SEBAGAI MATERIAL ADSORBEN CO2 - HIMAYA, MEISUN; Anggorowati, Dwi Ana; Rahman, Nanik Astuti (jurnal ATMOSPHERE, 2025)
Silica sand has physical and chemical characteristics that make it a potential candidate as an adsorbent material. This research utilises silica sand waste from PT DPL sandblasting using the in-situ method with amine group modification to determine its CO2 adsorbent potential along with the effect of amine group ratio: solvent and acid concentration on CO2 absorption. Silica sand waste was extracted using NaOH to obtain Sodium Silicate then modified with amine groups in this case -aminopropyl-triethoxysilane (APTS) by in-situ method and characterised by FTIR and SEM. Based on the results of FTIR analysis, the more amine groups in the APTS: ethanol ratio, the higher the possibility of interaction between amine groups and CO2. So that the modification of silica sand waste is potential as a CO2 adsorbent. The ratio of APTS: ethanol solvent with the most optimal results at a ratio of 1: 1. Based on the results of SEM analysis, the higher the concentration of HCl addition, the more optimal the modified silanol groups with amine groups. In this case the addition of HCl is most optimal at a concentration of 3N.